Les meurtres commis par des enfants en France au XIXe siècle : une étude sociale - Thomas Fadlallah (Criminocorpus)
On the 12th of February 1992 in Bootle, near Liverpool, two ten-year-old boys abducted, tortured and murdered James Patrick Bulger, aged two. Those two boys, Robert Thompson and Jon Venables, reminded public opinions all over the globe that children kill. The tables of the Gazette des Tribunaux list twenty-six cases of murders and murder attempts committed by children under fifteen between 1825 and 1914. The study of the judicial files that have been preserved allows us to bring to light the historic and social framework within which those crimes could arise. To do so, one has to depart from the judicial approach of crimes, which leads to bind the criminal ever tighter to his or her crime, and to consider that the first culprit of any crime is the institutional network within which it took place. Our aim is to show how some environments, historically situated, can be so crime-inducing that they trigger criminal behaviours even in populations that are a priori not prone to adopt them.